Uterine Smooth Muscle Tumor of Uncertain Malignant Potential (STUMP) Treated with Conservative Surgery: Systematic Review of Reproductive Outcomes - Martina Arcieri; Stefano Cianci; Canio Martinelli; Silvana Parisi; Stefano Pergolizzi; Vito Andrea Capozzi; Marco La Verde; Carlo Ronsini; Stefano Restaino; Giuseppe Vizzielli; Vittorio Palmara; Roberta Granese; et al. (Clinical and Experimental Obstetrics & Gynecology)
Background: Uterine smooth muscle tumors of uncertain malignant potential (STUMPs) are a rare tumor that represent a diagnostic challenge to both clinicians and pathologists. Hysterectomy is considered the definitive treatment in women who don’t desire to conceive anymore; while myomectomy is suggested in young women who desire to preserve their fertility. The aim of this review is to evaluate the reproductive outcomes in patients submitted to fertility sparing treatment and with a diagnosis of STUMP at the definitive pathological evaluation. Methods: We searched among electronic databases from inception of them through January 2022. The research was conducted using meshes created by the combination of relevant heading term, key words, and word variants for: “uterine smooth muscle tumor of uncertain malignant potential”, “fertility”, “pregnancy”. Results: Seven retrospective studies including 80 women desirous of conceiving after a diagnosis of STUMP were included in this systematic review. Among these, 33 (41.25%) women got pregnant at least once and we recorded a total number of pregnancies of thirty-nine. Almost all deliveries were performed by caesarean section. Two (6.1%) relapses were diagnosed. Patients were submitted to hysterectomy and STUMP was confirmed as the final pathological diagnosis. The median follow-up in patients who delivered live babies was 61 months after surgery. At the last follow-up, all patients were alive without evidence of disease. Conclusions: This review shows that pregnacy seems to be possible and safe after the diagnosis of STUMP. These women should undergo rigorous follow-up and consider hysterectomy after completion of their reproductive plan. This review could be a useful tool for the counseling and the management of women with STUMP who desire to keep their fertility.